Young people’s transport and mobility in sub-Saharan Africa : the gendered journey to school - Porter, Gina; Hampshire, Kate; Abane, Albert; Tanle, Augustine; Munthali, Alister; Robson, Elsbet; Mashiri, Mac; Maponya, Goodhope (Documents d'Anàlisi Geogràfica, 2011)
This paper draws on rich ethnographic data and complementary survey research from a three-country study (Ghana, Malawi, South Africa) of young people’s mobility to explore the gendered nature of children’s journeys to school in sub-Saharan Africa. In most African countries, girls’ participation in formal education is substantially lower than boys’, especially at secondary school level. Transport and mobility issues often form an important component of this story, though the precise patterning of the transportation and mobility constraints experienced by schoolchildren, and the ways in which transport factors interact with other constraints, varies from region to region. We draw attention to the nature of gendered travel experiences in rural and urban areas, the implications of these findings for access to education, and finally suggest areas where policy intervention could be beneficial.